PSAK 73 and Changes to the Structure of Financial Statements: Is Transparency Increasing or Just a Reclassification? - Gabriel Ananta; Stevi Natasia Chandritike; Yusnaini Yusnaini (CV. KAMPUS AKADEMIK PUBLISING, 2026)
The convergence of global accounting standards is driving fundamental changes in financial reporting through the adoption of IFRS-based standards aimed at improving the quality and transparency of corporate financial information. Modern lease accounting standards, based on IFRS 16, change the approach to recognizing lease transactions by requiring the recognition of right-of-use assets and lease liabilities in the company's statement of financial position. This change arose in response to the weaknesses of the previous standard, which allowed off-balance sheet financing practices, resulting in economic liabilities not being fully reflected in the balance sheet. This study aims to evaluate whether changes in the structure of financial statements resulting from the adoption of modern lease standards actually improve financial statement transparency or merely represent a change in the classification of accounting presentation. The research method uses a systematic literature review of international academic research related to the impact of IFRS 16 on the quality of financial reporting and corporate financial ratios. The results of the study indicate that the implementation of IFRS 16 generally improves financial statement transparency by increasing the disclosure of economic liabilities and improving the quality of corporate leverage information. However, this standard also increases reporting complexity and expands management's judgment room in estimating lease terms and discount rates.